Children’s Social Interaction in the Adaptation Process Due to Parent’s Job Mobility - Wiraputra, Rahmi Hamidah; Dimyati, Dindin (Humaniora: Journal of Indonesia Culture and Society, 2026)
This research examines how parents' occupational mobility affects children's social relationships as they adjust to a new environment. Over 5.2 million people in Indonesia migrate between provinces to find work, of whom 36% have children under 18. Such a phenomenon leads to social and cultural adaptation problems for about 2.1 million children every year. Among the negative effects are difficulty with socialisation, loneliness, low self-esteem, and various developmental maladies, all of which stem from cultural, language, and communication differences in the new place. Results from the researcher's preliminary survey also confirm barriers to initial social interaction among children. Accordingly, this research uses constructive qualitative phenomenology to assess the social adaptation experiences of children of circular migrant workers. The data are collected through semi-structured online interviews with five informants (aged 20–22) based on specific criteria and are supplemented by observation and documentation. Data analysis follows the Miles and Huberman interactive model (collection, reduction, presentation, and conclusion) with source validity triangulation. Research findings indicate that the social adaptation of children of circular migrant workers is mediated by the quality of parenting, which instills social values to guide adaptation; cognitive abilities, such as self-efficacy and cognitive flexibility; and active communication strategies. The children develop language and interactional adjustment patterns based on Interaction Adaptation Theory to achieve social synchrony while drawing social capital from peer networks and significant figures such as teachers and parents.